An RTLS-Based Approach to Cyber-Physical Systems Integration in Design and Construction. (25th December 2012) - Akanmu, Abiola A.; Anumba, Chimay J.; Messner, John I.
Abstract : There have been several approaches to integrating physical construction components and their virtual models using RFID tags. These enable the movement of components to be tracked on the construction site. However, there is inadequate support for bidirectional coordination between these components and their virtual representations. Also, these approaches often involve manual input of status information into the tags and do not support tracking the permanent installed position of tagged components for consistency maintenance between the as-built and the as-planned models. As such, there are difficulties with ensuring accurate and timely updating of building information models and tag information during the construction process. A major bottleneck in achieving this integration is the choice of appropriate mechanisms for binding physical components with their virtual representations. This paper presents an approach to facilitating bidirectional coordination between physical construction components and their virtual models. Specialized real-time location sensing (RTLS) tags were used for tracking the position and status of physical construction components. This approach showed significant opportunities for enhancing real-time construction consistency checking, which will aid proactive decision making and control. The paper also discusses experiments undertaken to demonstrate the proposed RTLS-based system and highlights the merits and demerits of adopting the proposed approach on a full-scale project.